2010
DOI: 10.1158/1078-0432.ccr-09-1903
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial of Gefitinib versus Docetaxel in Non–Small Cell Lung Cancer Patients Who Have Previously Received Platinum-Based Chemotherapy

Abstract: Purpose: The ISTANA (IRESSA as Second-line Therapy in Advanced NSCLC-KoreA) study compared gefitinib with docetaxel in patients with advanced or metastatic non-small cell lung carcinoma (NSCLC) pretreated with platinum-based chemotherapy.Experimental Design: We conducted a multicenter, randomized, open-label phase III trial of gefitinib (250 mg/d) versus docetaxel (75 mg/m 2 day 1 every 3 weeks) in patients with advanced or metastatic NSCLC treated with one previous platinum-based chemotherapy. The primary end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
114
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 16 publications
0
114
0
Order By: Relevance
“…17,20 More recently, ISTANA (IRESSA as Second-Line Therapy in Advanced NSCLC-Korea) showed longer PFS and a significantly improved overall response rate compared with docetaxel in Korean patients. 21 It is unclear why no survival benefit with gefitinib was found in the Iressa Survival Evaluation in Lung Cancer study, despite apparent similar antitumor activity as that seen in previous studies with erlotinib. Several possible explanations can be considered, such as suboptimum dosing and enrollment of highly refractory cases.…”
Section: Discussionmentioning
confidence: 91%
“…17,20 More recently, ISTANA (IRESSA as Second-Line Therapy in Advanced NSCLC-Korea) showed longer PFS and a significantly improved overall response rate compared with docetaxel in Korean patients. 21 It is unclear why no survival benefit with gefitinib was found in the Iressa Survival Evaluation in Lung Cancer study, despite apparent similar antitumor activity as that seen in previous studies with erlotinib. Several possible explanations can be considered, such as suboptimum dosing and enrollment of highly refractory cases.…”
Section: Discussionmentioning
confidence: 91%
“…4, 8 ,9 Furthermore, as second-line chemotherapy, a phase III study demonstrated superior PFS with gefitinib than docetaxel for unselected patients in Korea . 10 . Thus, gefitinib is useful for the firstand second-line treatment of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta analysis of clinical trials of adjuvant therapy regimens in NSCLC involving .7,000 individuals, first published online in 2008, significant improvements in disease-free survival were demonstrated with relative risks ranging from 0.88 to 0.89 [77]. A more recent literature search of all randomised controlled trials that studied novel adjuvant therapies for patients with NSCLC showed that in 14 studies involving .15,000 patients [78][79][80][81][82][83][84][85][86][87][88][89][90][91], a statistically significant treatment effect on progression-free survival was seen with hazard ratios ranging from 0.6 to 0.83, with a single exception [90] in which the hazard ratio in favour of therapy was reduced to 0.37.…”
Section: The Current Uncertainty About How To Measure Efficacy In Trimentioning
confidence: 99%